Focal atrial tachycardia-the localization differences between men and women: A study of 487 consecutive patients - Yusuf Turkmen; Per Insulander; Hamid Bastani; Nikola Drca; Ott Saluveer; Jari Tapanainen; Tara Bourke; Göran Kennebäck; Jonas Schwieler; Frieder Braunschweig; Mats Jensen-Urstad (Anatolian Journal of Cardiology)
Objective: The preferential sites for focal atrial tachycardia (FAT) are mainly in the right atrium in both sexes. However, a limited number of studies have indicated that sex differences in the localization of FAT. This study investigated possible sex differences in the distribution of FAT in a large cohort of patients referred for ablation. Methods: From 2004 to 2019, 487 patients (298 women) were referred to our institution for ablation of FAT. A standard electrophysiological study was conducted, and isoproterenol or atropine was given when needed. Conventional catheter mapping, electroanatomic contact mapping, and noncontact mapping were used to assess the origin of ectopic atrial tachycardia. Results: Overall, 451 foci were successfully ablated in 436 patients (90%). Although the foci located along the crista terminalis were more common in women than in men (42% vs. 29%; p=0.023), the opposite were found in the foci located along the tricuspid annulus (5% vs. 11%; p=0.032) and the right atrial appendage (RAA) (1% vs. 3%; p=0.032). Other locations were similarly distributed in men and women. In addition, the presence of persistent FAT was more frequent in men than in women (22% vs. 5%; p<0.001). Finally, the difference in the induction pattern of FAT was also remarkable between sexes. Conclusion: The distribution of FAT in women and men is different. In addition, persistent FAT seems more often in men than in women. The different distribution, persistency, and induction pattern of FAT should be considered in the successful management of this type of tachycardia.